2019
DOI: 10.3390/md17040204
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Approaches to Generating and Identifying Angiotensin-Converting Enzyme I Inhibitory Peptides from Green Macroalga Ulva lactuca

Abstract: A protein extract was generated from the macroalga Ulva lactuca, which was subsequently hydrolysed using the food-grade enzyme papain and angiotensin-converting Enzyme I and renin inhibitory peptides identified using a combination of enrichment strategies employing molecular weight cutoff filtration and mass spectrometry analysis. The generated hydrolysates with the most promising in vitro activity were further purified using preparative RP-HPLC and characterised. The 1 kDa hydrolysate (1 kDa-UFH), purified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 49 publications
1
45
0
Order By: Relevance
“…Moreover, it is the least expensive source of protein, which may be helpful in solving feeding and agronomical problems [44]. However, hydrolysis of proteins, also these from soybean, contributes to the production of peptides that taste bitter and are not accepted by Western consumers, even if they offer a health-beneficial value [45,46]. Our initial bioinformatic predictions also confirmed the potential of soybean proteins as the richest sources of bitter-tasting sequences when comparing them to the other sequences of proteins derived from grains, oil, and leguminous plants (21 sequences in total; data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is the least expensive source of protein, which may be helpful in solving feeding and agronomical problems [44]. However, hydrolysis of proteins, also these from soybean, contributes to the production of peptides that taste bitter and are not accepted by Western consumers, even if they offer a health-beneficial value [45,46]. Our initial bioinformatic predictions also confirmed the potential of soybean proteins as the richest sources of bitter-tasting sequences when comparing them to the other sequences of proteins derived from grains, oil, and leguminous plants (21 sequences in total; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The BIOPEP-UWM database was applied to predict the umami taste of peptides derived from clam M. meretrix Linnaeus [64]. Garcia-Vaquero et al [45] applied the hybrid approach to assess the bitter taste properties of novel peptide ACE inhibitors derived from U. lactuca (green algae). To this end, green algae proteins were in vitro (enzyme used: papain) and in silico (tool used: PeptideCutter) hydrolyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, membrane filtration was applied with three MWCO, i.e., 10, 3, and 1 kDa, when processing an U. lactuca protein hydrolysate at laboratory-scale. The 3 kDa permeate fraction had the highest renin inhibitory activity [71]. On the other hand, Beaulieu et al [85] reported that the >10 kDa (retentate) of Saccharina longicruris hydrolysates exhibited higher antibacterial activity compared to <10 kDa permeate fraction.…”
Section: Membrane Separationmentioning
confidence: 98%
“…A total of 21 potential ACE inhibitory peptides from a thermolysin hydrolysate of Grateloupia asiatica, aqueous extracts were identified using the ExPASy PeptideCutter tool (https://web.expasy.org/ peptide_cutter/) [108]. In a study by Garcia-Vaquero et al [71], the ExPASy PeptideCutter tool was used to simulate the in silico digestion of 48 peptides identified in a hydrolysate of U. lactuca resulting in the identification of 16 peptides with potential ACE and renin inhibitory activity based on information provided in the BIOPEP database and PeptideRanker. The BIOPEP database was also used to indicate that AVVK and VIAE identified in a hydrolysate of Mastocarpus stellatus had previously been reported as antibacterial peptides [100].…”
Section: In Silico Analysismentioning
confidence: 99%